PEMBERDAYAAN KELOMPOK TANI PADI DI DESA IKHWAN KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - NURHAMIDIN, ANISA NURHANIFAH; TULUSAN, FEMMY; RURU, JOORIE (Sam Ratulangi University, 2020)
Farmer empowerment is all efforts to improve the ability of farmers to carry out better farming througheducation and training, counseling and assistance, development of systems and means of marketingagricultural products, consolidation and guarantee of agricultural land area, easy access to knowledge,technology and information, and strengthening farmer institutions. Farmer group is a social unitconsisting of two or more people who carry out intensive and regular interactions, so that between themthere is a division of tasks, structures, and certain norms that are specific to that unity. In this studyusing a type of qualitative research in which this research is descriptive in nature that is conducting indepthinterviews collecting primary data and collecting secondary data, which then results of primaryand secondary data are processed and data will be obtained. The results showed that the problem thathampered the empowerment of rice farmers in the Ikhwan Village was the assistance program providedby the government such as rice seedlings that were not well suited to the soil structure in the IkhwanVillage and with the inappropriate assistance had an impact on the quality of crops that were not goodfor farmers rice in the Ikhwan Village. The government had already provided training on good farmingpractices and pest management, but that had taken place 4 years ago. The problem hampering theempowerment of farmer groups in the Ikhwan village is also about the scarce fertilizer and the pricethat is difficult for farmers to reach because of the scarcity of fertilizer. The government has also soughta way out so that the rice farmers' group in the Ikhwan village does not have a dispute because of theimpact of the government assistance program. Finally, due to the lack of training provided by thegovernment, only farmer group meetings were held to discuss the problems faced by rice farmers in theIkhwan village.Keywords: Empowerment, Farmer Group, Program.